A Single Angiotensin II Hypertensive Stimulus Is Associated with Prolonged Neuronal and Immune System Activation in Wistar-Kyoto Rats - Zubcevic, Jasenka; Santisteban, Monica M.; Perez, Pablo D.; Arocha, Rebeca; Hiller, Helmut; Malphurs, Wendi L.; Colon-Perez, Luis M.; Sharma, Ravindra K.; de Kloet, Annette; Krause, Eric G.; Febo, Marcelo; Raizada, Mohan K. (Frontiers in Physiology, 2017)
Activation of autonomic neural pathways by chronic hypertensive stimuli plays a significant role in pathogenesis of hypertension. Here, we proposed that even a single acute hypertensive stimulus will activate neural and immune pathways that may be important in initiation of memory imprinting seen in chronic hypertension. We investigated the effects of acute angiotensin II (Ang II) administration on blood pressure, neural activation in cardioregulatory brain regions, and central and systemic immune responses, at 1 and 24 hour post-injection. Administration of a single bolus intra-peritoneal (I.P.) injection of Ang II (36 µg/kg) resulted in a transient increase in the mean arterial pressure (MAP) (by 22±4 mmHg vs saline), which returned to baseline within 1 hour. However, in contrast to MAP, neuronal activity, as measured by manganese-enhanced magnetic resonance (MEMRI), remained elevated in several cardioregulatory brain regions over 24 hours. The increase was predominant in autonomic regions such as the subfornical organ (SFO; 20%), paraventricular nucleus of the hypothalamus (PVN; 20%) and rostral ventrolateral medulla (RVLM; 900%), among others. Similarly, systemic and central immune responses, as evidenced by circulating levels of CD4+/IL17+ T cells, and increased IL17 levels and activation of microglia in the PVN respectively, remained elevated at 24 hours following Ang II challenge. Elevated Fos expression in the PVN was also present at 24 hours (by 73±11%) following Ang II compared to control saline injections, confirming persistent activation of PVN. Thus, even a single Ang II hypertensive stimulus will initiate changes in neuronal and immune cells that play a role in the developing hypertensive phenotype.